Understanding Pre-Service Teachers’ Attitudes on Inclusive Education - Aji Ega Nabilla Putri; Khusnul Khatimah; Ade Ismail Ramadhan Hamid (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examines pre-service teachers’ attitudes toward inclusive education at Universitas Muhammadiyah Kalimantan Timur. A quantitative descriptive approach was employed to explore how future teachers perceive inclusive practices and how these perceptions may influence classroom implementation. Data were collected from 40 pre-service teachers using a 30-item questionnaire adapted from the Teacher Attitude to Inclusion Scale (TAIS). The instrument demonstrated good validity and high reliability, ensuring the accuracy and consistency of the data. Descriptive statistics and inferential analyses were conducted using SPSS to identify overall attitude trends and possible differences based on demographic factors, particularly gender. The findings indicate that pre-service teachers generally demonstrate positive attitudes toward inclusive education, reflecting an openness to accommodating students with diverse learning needs in regular classrooms. Statistical analysis reveals no significant difference in attitudes based on gender, suggesting that inclusive perspectives are shaped more by professional preparation and educational experiences than by demographic characteristics. Despite these positive attitudes, the results also highlight the need for increased practical exposure and classroom-based training to support effective implementation of inclusive practices in real teaching contexts. This study emphasizes the important role of teacher education programs in fostering not only positive attitudes but also practical competence through reflective learning, supervised practicum, and continuous professional development. The findings contribute to the growing discussion on inclusive teacher preparation and provide empirical evidence to support curriculum improvement in teacher education institutions.